Three-Dimensional High-Resolution Magnetic Resonance Imaging for the Assessment of Cervical Artery Dissection - Zhu, Xianjin; Shan, Yi; Guo, Runcai; Zheng, Tao; Zhang, Xuebin; Liu, Zunjing; Liu, Kunpeng (Frontiers in Aging Neuroscience, 2022)
Background and Purpose Diagnosing cervical artery dissection (CAD) is still a challenge based on the current radiographic criteria. This study aimed to assess the value of three-dimensional high-resolution magnetic resonance imaging (3D HRMRI) in the detection of the signs of CAD and its diagnosis. Materials and Methods Patients with CAD from January 2016 to January 2021 were recruited from our 3D HRMRI database. The signs of dissection (intramural hematomas, intimal flap, double lumen), length and location of the dissection, thickness of the intramural hematoma, intraluminal thrombus, and percentage of dilation of the outer contour of the dissection on 3D HRMRI were assessed. Results Fourteen patients with 16 CADs, including 12 carotid CADs and 4 vertebral CADs, were finally diagnosed in this study. On 3D HRMRI, intramural hematomas were detected in 13/16 (81.3%) lesions with high sensitivity (100%) and high specificity (100%). Intimal flaps were found in 9/16 (56.3%) lesions with moderate sensitivity (64.3%) and high specificity (88.9%). Double lumen signs were observed in 4/16 (25.0%) lesions with high sensitivity (80.0%) and high specificity (100%). In addition, concomitant intraluminal thrombus were detected in 4/16 (25.0%) lesions with high sensitivity (80.0%) and high specificity (100%). The mean length of dissection was (25.1 ± 13.7) mm. The mean thickness of the intramural hematoma was (4.3 ± 2.3) mm. The mean percentage of dilation for the outer contour of the dissection was (151.3 ± 28.6)%. Conclusion The 3D HRMRI enables detection of the dissecting signs, such as intramural hematoma, intimal flap, double lumen, and intraluminal thrombus with high sensitivity and specificity, suggesting a useful, and non-invasive tool for definitively diagnosing CAD.